Enhancing graduate employability through knowledge management. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2008)
An the recent 9th Malaysian Plan, one of the key thrusts focuses on Human Capital Development to increase the nation’s capacity for knowledge and innovation among the workforce. To achieve this, the Malaysian government has allocated over RM18 billion to increase access to higher education among youths from 29 per cent to 40 per cent by the year 2010 (Munir and Shukran, 2006). At the same time, the government intends to reduce the current unemployment rate of an estimated 3.4 per cent (Department of Statistics Malaysia, 2007) by offering more job opportunities to fresh graduates and the unemployed. By managing knowledge that is taught in various higher education institutions (HEIs), graduates can be equipped with the right kind of knowledge and capabilities to make them employable.